2021
DOI: 10.3389/fphys.2021.692098
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Is Associated With Diminished Cardiovascular Response to Anticipatory Stress in Patients With Coronary Artery Disease

Abstract: BackgroundFatigue and psychophysiological reactions to mental stress are known to be problematic in coronary artery disease (CAD) patients. Currently, studies exploring the relationship between fatigue and cardiovascular reactivity to stress are scarce and inconsistent. The current study aimed to investigate the links between cardiovascular response to mental stress and fatigue in CAD patients after acute coronary syndrome (ACS).MethodsThe cross-sectional study investigated 142 CAD patients (85% males, 52 ± 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Several studies in individuals with CAD suggested links between subjectively perceived stress and fatigue 31,32 . In terms of objectively observed psychophysiological stress markers, in our recent study 33 we found diminished cardiovascular reactivity to stress linked with higher levels of fatigue during anticipation of mental stress challenge, suggesting fatigue as a possible variable contributing to dysregulated psychophysiological response to stress in those after recent ACS. Nevertheless, even though the interplay between cortisol stress reactivity and fatigue has been extensively studied in persons with chronic fatigue syndrome [34][35][36] , there was no study that explored cortisol response to psychosocial stress and its interplay with fatigue in individuals with ACS.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Several studies in individuals with CAD suggested links between subjectively perceived stress and fatigue 31,32 . In terms of objectively observed psychophysiological stress markers, in our recent study 33 we found diminished cardiovascular reactivity to stress linked with higher levels of fatigue during anticipation of mental stress challenge, suggesting fatigue as a possible variable contributing to dysregulated psychophysiological response to stress in those after recent ACS. Nevertheless, even though the interplay between cortisol stress reactivity and fatigue has been extensively studied in persons with chronic fatigue syndrome [34][35][36] , there was no study that explored cortisol response to psychosocial stress and its interplay with fatigue in individuals with ACS.…”
mentioning
confidence: 75%
“…The MFI-20 covers five subscales: (1) general fatigue, (2) physical fatigue, (3) mental fatigue, (4) reduced activity, and (5) reduced motivation. Each domain consists of four items with possible answers on a five-point Likert scale (1 = “yes, that is true”; 5 = “no, that is not true”) 33 . The domain of General fatigue is composed of the general statements about fatigue and reduced functioning, covering physical as well as psychological aspects of fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies in individuals with CAD suggest links between subjectively perceived stress and fatigue 27,28 . In terms of objectively observed psychophysiological stress markers, in our recent study 29 we found that in individuals with CAD after ACS the diminished cardiovascular reactivity to stress was linked with higher levels of fatigue during anticipation of mental stress challenge, suggesting fatigue as a possible variable that may contribute to dysregulated psychophysiological response to stress. Nevertheless, even though the interplay between cortisol stress reactivity and fatigue has been extensively studied in persons with chronic fatigue syndrome [30][31][32] , to our knowledge, there is no study that explored cortisol response to psychosocial stress and its interplay with fatigue in individuals with ACS.…”
Section: Introductionmentioning
confidence: 92%
“…The MFI, consisting of 20 items covers ve subscales: (1) general fatigue, (2) physical fatigue, (3) mental fatigue, (4) reduced activity, and (5) reduced motivation. Each domain consists of four items with possible answers on a ve-point Likert scale (1 = "yes, that is true"; 5 = "no, that is not true") 29 . The domain of General fatigue is composed of the general statements about fatigue and reduced functioning, covering physical as well as psychological aspects of fatigue.…”
Section: State-trait Anxiety Inventory the State-trait Anxiety Invent...mentioning
confidence: 99%
“…38 Although our study did not adjust statistically for subjective efforts, other comparable studies have, and significant associations remained for fatigue, anxiety, and depressive symptoms. 20,39 Whereas it was beyond the scope of this study to identify causal pathways, future research should aim to identify biological mechanisms that underlie our results. It could be that individuals with relatively lower HR or BP who show low reactivity are more resistant to the physiological impacts of mild stressors, and this low reactivity would likely be associated with positive outcomes.…”
Section: Cardiovascular Stress Reactivity and Future Fatigue Anxiety ...mentioning
confidence: 99%